PENGARUH KOMPETENSI WIRAUSSAHA TERHADAP KEBERHASILAN USAHA DAGANG DI PASAR HELEZALULU KECAMATAN LAHUSA - Hiasman Halawa (Universitas Nias Raya, 2026)
In this case it can be explained that competition in entrepreneurship influences the success of trading businesses in the local market. Lahusa. In this case, several types are used, namely the quantitative method. The data source taken in this research is in accordance with the behavior of trading businesses by conducting and submitting questionnaires to a population and sample of 39 respondents. In this analysis, various methods are used, namely regression analysis. The results obtained are (1) business success, especially in the Helezalulu Market, so every entrepreneur needs to form a strategy first to launch the business. (2) Entrepreneurs must be able to channel business capital to prevent failure in entrepreneurship. (3) In order to achieve business success, the facilities needed by entrepreneurs should be provided to increase their experience in entrepreneurship. (4) Business conditions will improve when business actors provide good service to buyers and are supported by business capital.